UNIT 9.28 Molecular Diagnosis of Cystic Fibrosis. (1st January 2016) - Deignan, Joshua L.; Grody, Wayne W.
Abstract : This unit describes a recommended approach to identifying causal genetic variants in an individual suspected of having cystic fibrosis. An introduction to the genetics and clinical presentation of cystic fibrosis is initially presented, followed by a description of the two main strategies used in the molecular diagnosis of cystic fibrosis: (1) an initial targeted variant panel used to detect only the most common cystic fibrosis‐causing variants in the CFTR gene, and (2) sequencing of the entire coding region of the CFTR gene to detect additional rare causal CFTR variants. Finally, the unit concludes with a discussion regarding the analytic and clinical validity of these approaches. © 2016 by John Wiley & Sons, Inc.